If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 = 3u + 7 Reorder the terms: 1 = 7 + 3u Solving 1 = 7 + 3u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-3u' to each side of the equation. 1 + -3u = 7 + 3u + -3u Combine like terms: 3u + -3u = 0 1 + -3u = 7 + 0 1 + -3u = 7 Add '-1' to each side of the equation. 1 + -1 + -3u = 7 + -1 Combine like terms: 1 + -1 = 0 0 + -3u = 7 + -1 -3u = 7 + -1 Combine like terms: 7 + -1 = 6 -3u = 6 Divide each side by '-3'. u = -2 Simplifying u = -2
| -4(3-8n)=148 | | 2(-9x^2-3x+2)= | | X-4+3x+36=180 | | 30b^2+b-20=0 | | 2y-80=-3y-18 | | -9x^2+9x+1=0 | | 3.25z-(-.33+1.25z)=5.33 | | 6t^2-55t=-9 | | 2(x-1)+6y=-10 | | f(-3)=5x^3-2x^2-7x+2 | | 16x*(-2)=144 | | 2/5x.12= | | f(x)=5x^3-2x^2-7x+2f(-3) | | 10(1.6)-7y=-18 | | 3.25x-(.33+1.25x)=5.33 | | -0.2-2.6v=8.38 | | 2d^2+48d+46=0 | | x^2+3x+12=90 | | c-17=3.4 | | 3.4y-8=12 | | -2y-(-4y)= | | 8x+2(8.5)=30 | | 16=x-x-x+3+4+2 | | 3x=5x+6(2-x) | | 125x=17.50x+3.50 | | 7+2y=24 | | 6.3m+5=66 | | 0.04(y-8)+0.20y=0.06y-0.5 | | (x-3)(x-3)(x-3)-25=0 | | 4+2(3x-5)=3x+11 | | -6(0)+3y=-12 | | 5x^2=19x^2-12 |